2017
DOI: 10.3390/s17122739
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer and Colitis Diagnosis Using Fourier Transform Infrared Spectroscopy and an Improved K-Nearest-Neighbour Classifier

Abstract: Combining Fourier transform infrared spectroscopy (FTIR) with endoscopy, it is expected that noninvasive, rapid detection of colorectal cancer can be performed in vivo in the future. In this study, Fourier transform infrared spectra were collected from 88 endoscopic biopsy colorectal tissue samples (41 colitis and 47 cancers). A new method, viz., entropy weight local-hyperplane k-nearest-neighbor (EWHK), which is an improved version of K-local hyperplane distance nearest-neighbor (HKNN), is proposed for tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
(25 reference statements)
2
13
0
Order By: Relevance
“…Confirming the results of recent studies [ 47 , 54 ], decreased peaks related to lipids were found at 1742 cm −1 and 1400 cm −1 , and those related to carbohydrates were found at 1160 cm −1 . The increase in the amide I band (1642 cm −1 ) and amide II band (1550 cm −1 ) can be related to changes in the relative amounts of proteins in the cancer cells during cancer progression [ 55 ] and potentially be caused by the unregulated production of cell cytoplasm contents. The decreased peak intensity of the C=O band (1742 cm −1 ) in the cancer sample spectra can be correlated with a higher energy demand during cell proliferation that results in the metabolisation of fats [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Confirming the results of recent studies [ 47 , 54 ], decreased peaks related to lipids were found at 1742 cm −1 and 1400 cm −1 , and those related to carbohydrates were found at 1160 cm −1 . The increase in the amide I band (1642 cm −1 ) and amide II band (1550 cm −1 ) can be related to changes in the relative amounts of proteins in the cancer cells during cancer progression [ 55 ] and potentially be caused by the unregulated production of cell cytoplasm contents. The decreased peak intensity of the C=O band (1742 cm −1 ) in the cancer sample spectra can be correlated with a higher energy demand during cell proliferation that results in the metabolisation of fats [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, ovarian cancer patients with BRCA mutations or homologous recombination deficiency acquire therapeutic benefits from platinum drugs and PARP inhibitors, while immune checkpoint inhibitors are available for tumors with microsatellite instability. 32 As a convenient, sensitive and rapid technique, FTIR spectroscopy has also been indicated to be valuable and widely used in multiple tumors, such as in the diagnosis of lung, 33 breast, 34 colorectal, 35 , 36 cervical, 37 gastric, 38 liver 39 and thyroid tumors. 40 …”
Section: The Application Of Ftir Spectroscopy In the Diagnosis Of Ovamentioning
confidence: 99%
“…Zhi et al 21 used a support vector machine (SVM) classifier for the prediction of the metastasis of CRC. Li et al 24 used an improved k-nearest neighbors classifier to diagnose CRC and colitis with Fourier transform infrared spectroscopy. Long et al 25 examined the random forest, logistic regression, naïve Bayes, and k-nearest neighbors models and multi-platform transcriptomics to introduce novel signatures for the accurate diagnosis of CRC.…”
Section: Introductionmentioning
confidence: 99%